Degradasi Zat Warna Malachite Green Secara Ozonolisis Dengan Penambahan Katalis TiO2-anatase dan ZnO - Bhayu Gita Bhernama (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Degradation of malachite green has been done. In this research, degradation process of malachite green was done by ozonolisis method, using TiO2- anatase and ZnO catalyst. The residu of malachite green was centrifuged and measured by spectroscopy UV / Vis at 200-800 nm after degradation. 6 mg / L malachite green diozonolisis for 5 minutes obtained pH optimum at pH 7. 6 mg / L malachite green was added 0.025 mg TiO2-anatase catalyst, and 0.025 mg ZnO at pH 7 with a variation time obtained optimum time of 5 minutes. Percent degradation of malachite green is generated by the addition of 0.0250 grams of TiO2-anatase 99.77% and 0.0250 grams of ZnO 93.59%. Percent of the results showed that the degradation of degradation with the addition of TiO2-anatase is greater than the addition of ZnO, because of the stability of TiO2- anatase is large.